Oscillation of nonlinear third order perturbed functional difference equations - Dinakar, P.; Selvarangam, S.; Thandapani, E. (Nonautonomous Dynamical Systems, 2019)
This paper deals with oscillatory and asymptotic behavior of all solutions of perturbed nonlinear third order functional difference equation By using comparison techniques we present some new sufficient conditions for the oscillation of all solutions of the studied equation. Examples illustrating the main results are included.